REVIEW PERAN VAKSIN DEMAM TIFOID UNTUK WISATAWAN DI DAERAH TROPIS - Lewi Santoso, Anna; Sanjaya, Ayling; Santoso , Jemima Lewi; Njoto, Ibrahim (Jurnal Medicare, 2025)
Typhoid fever is a systemic infectious disease caused by Salmonella enterica subspecies enterica serovar Typhi (S. Typhi). Transmission commonly occurs through food or drinks contaminated with the feces or urine of infected individuals. Travelers to endemic areas, particularly tropical regions, are at high risk of infection. Symptoms include high fever, nausea, and abdominal pain. Improvements in sanitation and hygiene have contributed to a decline in typhoid incidence; however, the effectiveness of antibiotic treatment is decreasing due to rising resistance. Vaccination has become a highly recommended preventive measure for both local populations and travelers. This study is a literature review of English-language articles published between 2014 and 2024, sourced from PubMed (106 articles), Google Scholar (915), and ProQuest (14), using the keywords “typhoid fever” and “vaccine.” A total of 49 relevant articles were analyzed. The results show that the World Health Organization (WHO) recommends typhoid vaccination in endemic areas. In conclusion, vaccination is effective in reducing morbidity and mortality rates and in preventing antibiotic resistance. Well-planned preventive strategies are essential for protecting public health.